The top row of matrix A (1, 2, 1) is multiplied with the first column of matrix B (1,0,-1) and the result is 1x1 + 2x0 + 1x -1 = 0 this is row 1 column 1 of the resultant matrix The top row of matrix A (1,2,1) is multiplied with the second column of matrix B (-1, -1, 1) and the result is 1 x-1 + 2 x -1 + 1 x 1 = -2 , this is row 1 column 2 of the resultant matrix Repeat with the second row of matrix A (-1,-1.-2) x (1,0,-1) = 1 this is row 2 column 1 of the resultant matrix, multiply the second row of A (-1,-1,-2) x (-1,-1,1) = 0, this is row 2 column 2 of the resultant Repeat with the third row of matrix A( -1,1,-2) x (1,0, -1) = 1, this is row 3 column 1 of the resultant the third row of A (-1,1,-2) x( -1,-1,1) = -2, this is row 3 column 2 of the resultant matrix